TRAP-1, THE MITOCHONDRIAL Hsp90 - Altieri, Dario C. (2011)
Protein folding quality control does not occur randomly in cells, but requires the action of specialized molecular chaperones compartmentalized in subcellular microenvironments and organelles. Fresh experimental evidence has now linked a mitochondrial-specific Heat Shock Protein-90 (Hsp90) homolog, Tumor Necrosis Factor Receptor-Associated Protein-1 (TRAP-1) to pleiotropic signaling circuitries of organelle integrity and cellular homeostasis. TRAP-1-directed compartmentalized protein folding is broadly exploited in cancer and neurodegenerative diseases, presenting new opportunities for therapeutic intervention in humans.